Current State of Innovation and Management Control, Ready Made Garments Industry Towards Circular Economy - Mohammed Masum Billah; Mohd Helmi Ali; Syed Shah Alam; Mazzlida Mat Deli (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study investigates the impact of innovative strategies and management control systems (MCS) on the implementation of circular economy (CE) practices within Bangladesh’s ready-made garment (RMG) sector. Utilizing the Resource-Based View (RBV), Natural Resource-Based View (NRBV), and Stakeholder Resource-Based View (SRBV), the study constructs a comprehensive framework that differentiates between internal innovation capabilities and externally acquired knowledge. Data were gathered from 142 management-level professionals using a standardized questionnaire and analyzed using PLS-SEM. The results indicate that open innovation and management control systems significantly enhance CE adoption, but green product and process innovation have favorable yet statistically negligible correlations. Moreover, MCS does not substantially influence the link between innovation and CE. The results indicate that, in buyer-driven and compliance-intensive sectors, the adoption of a circular economy is predominantly influenced by institutional factors rather than by organizational capabilities. The research enhances theoretical understanding by illustrating the contextual constraints of NRBV in low-autonomy supply chain settings and emphasizing the preeminent influence of external collaboration and compliance-driven governance. The findings indicate that organizations ought to prioritize strategic relationships and organized control systems rather than solitary internal innovation efforts to expedite circular transformation.